2022
DOI: 10.22541/au.165477064.44060389/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Affordable de novo generation of fish mitogenomes using amplification-free enrichment of mitochondrial DNA and deep sequencing of long fragments

Abstract: Biomonitoring surveys from environmental DNA make use of metabarcoding tools to describe the community composition. These studies match their sequencing results against public genomic databases to identify the species. However, mitochondrial genomic reference data are yet incomplete, only a few genes may be available, or the suitability of existing sequence data is suboptimal for species level resolution. Here we present a dedicated and cost-effective workflow with no DNA amplification for generating complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Although CRISPR is generally underutilized in environmental science (Phelps et al, 2020), CRISPR-based enrichment strategies have shown promise and versatility (Baerwald et al, 2023;López-Girona et al, 2020;Ramon-Laca et al, 2022;Sánchez et al, 2022;Sandoval-Quintana et al, 2023;Williams et al, 2023). We evaluated strategies to harness this power for important applications such as overcoming the plant DNA barcode resolution problem (CBOL Plant Working Group, 2009;Kress, 2017) and issues with PCR-based DNA relative read abundance calculations (Deagle et al, 2019;Littleford-Colquhoun, Freeman, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although CRISPR is generally underutilized in environmental science (Phelps et al, 2020), CRISPR-based enrichment strategies have shown promise and versatility (Baerwald et al, 2023;López-Girona et al, 2020;Ramon-Laca et al, 2022;Sánchez et al, 2022;Sandoval-Quintana et al, 2023;Williams et al, 2023). We evaluated strategies to harness this power for important applications such as overcoming the plant DNA barcode resolution problem (CBOL Plant Working Group, 2009;Kress, 2017) and issues with PCR-based DNA relative read abundance calculations (Deagle et al, 2019;Littleford-Colquhoun, Freeman, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while many previous studies have shown some degree of off-target enrichment when using single-species samples (López-Girona et al, 2020;Ramon-Laca et al, 2022), Sandoval-Quintana et al (2023) found that only 0.03% of good quality reads covered the region they wished to study when enriching a bacterial gene from a complex microbial sample. To address this challenge, it may be useful to experiment with mismatch tolerance values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raw sequencing data have been made available on Dryad, data set (Ramón-Laca et al, 2022), https://doi.org/10.5061/dryad.jm63x sjdj.…”
Section: Ack N O Wle D G E M Entsmentioning
confidence: 99%